Soil organic matter fractions and aggregate distribution in response to functional composition of plant communities - Bahrami, Behnam; Ghorbani, Ardavan; Jafari, Mohammad; Rezanezhad, Fereidon; Esmali, Abazar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2018)
Vegetation types are amongst the most relevant pedogenic factors controlling soil organic carbon. The impact of shrub encroachment (SE) on soil organic matter (SOM) of alpine grasslands has scarcely been investigated. We aimed to compare the effects of shrub invasion on soil carbon, nitrogen and organic matter in three representative communities. Three dominant plant communities representing low, intermediate and high SE were selected in alpine grassland habitats in north-western Iran. To compare the SOM parameters, soil samples from each community were collected from depths of 0-15 cm and 15-30 cm. The results showed that the spatial variation of SOM was probably affected by the shrub invasion. The highest values of total C and total N were observed in high SE (Pteropyrum aucheri community) and intermediate SE (Astragalus microcephalus community) as compared to low SE (Prangus uloptera community). Soil particulate organic matter for carbon and nitrogen were generally highest in the intermediate SE. There was a significantly smaller proportion of soil present as macro-aggregates and higher proportion of soil present as micro aggregates in the upper soil layer of intermediate SE as compared to the others, while no significant difference between micro- and macro-aggregates in the lower soil layer between plant communities were detected. Shrub functional groups in grassland communities should be considered in the interpretation of shrub encroachment influences on soil organic matter.